Introduction to cellular calcium signaling - Bootman, Martin (Henry Stewart Talks, 2007)
Introduction to the spatial and temporal complexity of cellular calcium signals, Calcium 'on' and 'off' mechanisms, The calcium signaling toolkit, Calcium sources, Calcium waves, Calcium oscillations, Cell-specific calcium signaling proteomes, Examples of calcium signaling differentially controlling cellular processes such as gene transcription and neuronal differentiation, Inositol 1,4,5-trisphosphate receptors as an example of a calcium release system, Mitochondrial calcium uptake, Regulation of apoptosis by calcium, Cardiac calcium signaling, Atrial myocytes regulate contraction by modulating the spatial properties of their calcium signals, Calcium-induced arrhythmias
Updated at 2012/07/15